2018
DOI: 10.1111/pim.12534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovar‐DRA and Ovar‐DRB1 genotype in small ruminants with haemonchosis

Abstract: The effect of Ovar-DRA and Ovar-DRB1 genotypes on faecal egg count (FEC) was determined in sheep and goats infected with Haemonchus contortus. One hundred and forty-three sheep from 3 different breeds (St. Croix, Katahdin and Dorper) and 150 goats from three different breeds (Spanish, Boer and Kiko) were used. Parasitological (FEC), haematological (packed cell volume) and immunological (IgA, IgG and IgM) parameters were measured. Sheep populations showed a higher FEC and humoural response than goat breeds. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…12,13 Several groups have shown associations between genetic variants in the MHC and faecal egg counts. 5,[14][15][16][17] In particular, the DRB1*11:01 allele has been associated with lower faecal egg counts in Scottish Blackface 5 and Suffolk sheep. 15 However, this association was not confirmed in a population of Texel sheep.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…12,13 Several groups have shown associations between genetic variants in the MHC and faecal egg counts. 5,[14][15][16][17] In particular, the DRB1*11:01 allele has been associated with lower faecal egg counts in Scottish Blackface 5 and Suffolk sheep. 15 However, this association was not confirmed in a population of Texel sheep.…”
Section: Introductionmentioning
confidence: 98%
“…The association between the MHC and nematode infection of sheep is one of the most convincing examples of an association with a major disease of livestock . Several groups have shown associations between genetic variants in the MHC and faecal egg counts . In particular, the DRB1*11:01 allele has been associated with lower faecal egg counts in Scottish Blackface and Suffolk sheep .…”
Section: Introductionmentioning
confidence: 99%
“…MHC genotype can impact on host responses to parasitic disease by influencing the range of antigenic peptides presented for recognition by the adaptive immune system. Numerous studies have shown the relevance of MHC diversity on resistance or susceptibility to infection with nematode parasites in many species including mice [25,26], sheep [8][9][10][11][12] and cattle [27]. However, MHC genotyping has relied on the availability of cell or tissue samples for DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…No specific DRB1 alleles have previously been associated with resistance to H. contortus infection although microsatellite [10] and single nucleotide polymorphisms within Ovar-DRB1 have been identified in resistant and susceptible sheep from St. Croix, Katahdin and Dorper breeds [12]. One DRB1 allele (11:01) has been associated in Suffolk sheep with lower worm burdens and higher mast cell and plasma platelet counts following infection with the GIN Teladorsagia circumcincta [36] and with reduced faecal egg count in Texel breed sheep [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation